2021
DOI: 10.3168/jds.2020-18691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local or systemic administration of meloxicam on mammary gland inflammatory responses to lipopolysaccharide-induced mastitis in dairy cows

Abstract: Nonsteroidal anti-inflammatory drugs (NSAID) are commonly used in combination with antimicrobial mastitis treatments to reduce pain. Little is known about whether meloxicam, an NSAID designed for the preferential inhibition of cyclooxygenase-2 over cyclooxygenase-1, affects the mammary immune response. The objective of this study was to analyze the mammary immune response to intramammary (local) or intravenous (systemic) administration of meloxicam with or without immune activation by lipopolysaccharide (LPS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Additional NSAIDs are currently being examined to improve inflammatory responses and milk production during mastitis and onset of lactation. However, inhibition of proper inflammatory function [ 60 ] and lack of effect on haptoglobin concentrations [ 61 ] further highlight the need for improved markers of inflammation and anti-inflammatory treatment. A better understanding of the inflammatory state of cows at the time of NSAID treatment has the potential to improve the clinical outcomes of severe coliform mastitis with systemic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Additional NSAIDs are currently being examined to improve inflammatory responses and milk production during mastitis and onset of lactation. However, inhibition of proper inflammatory function [ 60 ] and lack of effect on haptoglobin concentrations [ 61 ] further highlight the need for improved markers of inflammation and anti-inflammatory treatment. A better understanding of the inflammatory state of cows at the time of NSAID treatment has the potential to improve the clinical outcomes of severe coliform mastitis with systemic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…compared the changes in milk SCC in cows that were experimentally injected with intramammarily LPS and intravenously injected with MX to those injected with intramammarily LPS alone. Their results showed that MX did not significantly decrease SCC, with similar values 9 hr after injection [ 3 ]. They also reported that injecting MX alone into the udder did not affect SCC [ 3 ].…”
Section: Discussionmentioning
confidence: 98%
“…Their results showed that MX did not significantly decrease SCC, with similar values 9 hr after injection [ 3 ]. They also reported that injecting MX alone into the udder did not affect SCC [ 3 ]. In the present study, the LS for both groups were significantly lower ( P <0.01) on days 0 and 1 compared to day 3.…”
Section: Discussionmentioning
confidence: 98%
“…This response was different than 50 mg of intramammary ketoprofen, which limited the leukocyte infiltration after LPS challenge (Dan et al, 2018). In contrast, meloxicam promoted an earlier increase in SCC response when the mammary gland immune system was stimulated with a low dose of LPS (Caldeira et al, 2021). Other NSAID such as the nonselective diclofenac or the COX2-selective celecoxib impaired the mammary epithelial barrier in vitro by damaging the cells (Sintes et al, 2020).…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 95%